SHIFTING LANDSCAPES: THE IMPACT OF GLOBAL PANDEMIC ON REGIONAL DEVELOPMENT DISPARITIES AND FISCAL RESILIENCE - Gunawan, Gunawan; Juanda, Bambang; Pravitasari, Andrea Emma (LPPM Universitas Jambi, 2026)
This study analyzes regional development disparities and fiscal resilience in West Java Province, Indonesia, from 2014 to 2024, specifically focusing on the disruptive impact of the COVID-19 pandemic. Using the Williamson Index and a decomposed Theil Index across four spatial lenses: metropolitan vs. non-metropolitan, north vs. south, development areas, and cities vs. regencies. The research evaluates inequality trends and their determinants through panel data regression (Random Effects Model) for the 2018–2024 period. Results reveal that regional inequality remains high, with the Williamson Index peaking at 0.710 during the pandemic in 2020 and stagnating thereafter. Theil Index decomposition shows that intra-regional (within-area) disparity is the primary contributor to total inequality. Regression analysis indicates that the Human Development Index (HDI) and Non-Physical Special Allocation Funds (DAK) significantly improve GRDP per capita, while population density and poverty rates act as structural barriers. A notable novelty is the identification of a